PENGARUH KEBIJAKAN HUTANG, PROFITABILITAS DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN (Studi pada Sektor Properti, Real Estate dan Kontruksi Bangunan yang Terdaftar di Bursa Efek Indonesia periode 2020-2023) - Arniyawati Adinda Nur Aini; Ismunawan Ismunawan (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The purpose of this study is to determine the impact of debt, profitability, and liquidity one quity dividend policy in 2020-2023.This type of study uses quantitative data in the form of corporate financial reports. The population of this study is 80 companies in the real estate, property ,and building and construction sectors in 2020-2023 that are liste don the Indonesia Stock Exchange, i.e., a total sample size of 18 companies. The data sources used in this study are financial statements in the form of balance sheets, incomestatements, statements of changes in equity, cash flow statements, and reports on notes to financial statements. The results indicate that the debt/equityratio (DER) has appositive and significant effect to fincreasing dividend policy. Profitability / Returnonassets (ROA) has appositive and significant effect of increasing dividend policy. Liquidity / Current Ratio (CR) has a significant positive effect on dividend policy.